Energy and Environmental Sustainability of Malaysian Universities Through Energy Conservation Measures - Woan Wen, Tan; Palanichamy, C (International Journal of Energy Economics and Policy, 2018)
Curtin University Malaysia, a significant education service provider in Sarawak state has been identified as one of the foremost electrical energy consumers in the state. Though past studies made on the Curtin campus brought out attainable suggestions, and they were subsequently implemented, still the per capita energy consumption needs to be reduced further. Hence, this situation necessitated an in-depth energy audit to determine how and where the energy is being consumed economically and efficiently or wasted instead. This paper aims at energy conservation measures based on a comprehensive load profile study conducted on the university campus. Based on the findings of the study, cost-effective and time-bound energy conservation tactics are suggested for scheming and controlling Curtin's colossal energy expenses. Keywords: Energy audit, Measures of conservation, Energy cost and environmental benefits. JEL Classifications: Q28, Q48, Q58 DOI: https://doi.org/10.32479/ijeep.7006